Tournament Incentives and Firm Innovation - Shen, Carl Hsin-han; Zhang, Hao (Review of Finance, 2018)
Abstract This study analyzes how promotion-based tournament incentives for non-CEO senior executives affect corporate innovation. We measure tournament incentives using the pay gap between a CEO and the next layer of senior executives. We find that tournament incentives are positively related to innovative efficiency, as measured by the number of patents and patent citations generated per million dollars of R&D expense. Our main finding holds in an instrumental-variable analysis and regressions using alternative innovation measures, including patent generality and originality indices and stock market reactions to patent grants. Consistent with prior theories, the positive effect of tournament incentives is found to be particularly pronounced during the period prior to CEO turnovers.